Investigating Roles of Self-Efficacy on Mobile Games Adoption in Indonesia - Putu Adi Putra Arimbawa; Mardhatillah Shanti; Febby Candra Pratama (Universitas Airlangga, 2020)
The gaming industry has become one of the most promising markets, and playing a game is also has been considered as the best leisure and entertainment activities in the last few decades. Understanding how consumers within the market behave is important to decide the best marketing strategy to be applied to achieve a competitive advantage in the market. Technology Acceptance Model (TAM) has been widely used to examine the adoption of technology and/or information system-related products. This study's main purpose is to investigate player’s intention to play games on a mobile platform in Indonesia. We predict self-efficacy as the keys determinant factor that could affect player’s adoption of mobile games. Data calculation conducted by utilizing SmartPLS 3.2. The finding of this study proved that self-efficacy is a strong determinant of players’ mobile game adoption. Besides, we found interesting results in which perceived ease of use and attitude toward use did not have a significant direct effect on players’ intention to play mobile games. Theoretically, this study provides an integrated conceptual model to explain the role of self-efficacy on mobile game adoption. Strategically, this study results could help mobile game marketers to build the best marketing strategy for their targeted players.